Applying the CRISP tool in Bolivia and Zambia: Identifying climate risks and adaptation options in agricultural and food system projects - Heber, Alina; Lottje, Christine; Below, Till; Voss, Maike; Rued, Soeren; Saavedra, Carlos; Bwalya, Able; Chikomba, Patrick; Bonilla Findji, Osana (2024)
CRISP, the Climate Risk Planning & Managing Tool for development programmes in agri-food systems, helps practitioners and policy makers in the agri-food sector to understand climate related risks, and to identify relevant adaptation options for their specific agricultural systems. This publication illustrates the practical application of the CRISP tool in Bolivia and Zambia. To show potential users what the tool can do, and which impacts it has already generated, two projects are presenting their findings in this factsheet. The first example from Bolivia illustrates how valuable the CRISP tool application can be in the planning phase of a project. The second case from Zambia highlights the benefits of the tool outcomes for the verification of activities that are already being implemented. The CRISP tool specifically addresses project managers and practitioners in agriculture, rural development and food and nutrition security projects. CRISP guides the user through a process to understand climate related risks associated with specific agricultural systems, articulate science-based adaptation hypotheses, identify cascading impacts and review relevant adaptation options. The tool was developed by the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) on behalf of the German Federal Ministry for Economic Cooperation and Development (BMZ), in cooperation with Eurac Research and the Alliance of Bioversity International and the International Centre for Tropical Agriculture (CIAT).